Population Diversity, Dynamics, and Differentiation of Wheat Stripe Rust Pathogen Puccinia striiformis f. sp. tritici From 2010 to 2017 and Comparison With 1968 to 2009 in the United States - Bai, Qing; Wan, Anmin; Wang, Meinan; See, Deven R.; Chen, Xianming (Frontiers in Microbiology, 2021)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is a serious disease on wheat in the United States, especially after 2000. In the present study, 2,247 Pst isolates collected over all stripe rust epidemiological regions in the United States from 2010 to 2017 were genotyped at 14 simple sequence repeat (SSR) loci to investigate the population diversity, dynamics, and differentiation. A total of 1,454 multi-locus genotypes (MLGs) were detected. In general, the populations in the west (Regions 1 to 6) had more MLGs and higher diversities than the populations in the east (Regions 7 to 12). The populations of 2010 and 2011 were more different from the other years. Genetic variation was higher among years than among regions, indicating the fast changes of the population. The divergence (Gst) was bigger between the west population and east population than among regions within either the west or east population. Gene flow was stronger among the regional populations in the east than in the west. Clustering analyses revealed 3 major molecular groups (MGs) and 10 sub-MGs by combining the genotypic data of 2010-2017 isolates with those of 1968-2009. MG1 contained both 1968-2009 isolates (23.1%) and 2010-2017 isolates (76.9%). MG2 had 99.4% isolates from 1968-2009. MG3, which was the most recent and distinct group, had 99.1% isolates from 2010-2017. Of the 10 sub-MGs, 5 (MG1-3, MG1-5, MG3-2, MG3-3, and MG3-4) were detected only from 2011-2017. The SSR genotypes had a moderate, but significant correlation (r = 0.325; P < 0.0001) with the virulence phenotype data. The standard index values of association (rbarD = 0.11) based on either regional or yearly populations suggests clonal reproduction. This study indicated high diversity, fast dynamics, and various levels of differentiation of the Pst population over the years and among epidemiological regions, and the results should be useful for managing wheat stripe rust.